Perbandingan Algoritma RED, SFQ, Dan AQM Pada Jaringan Enterprise Dengan Vmware ESXI Dan Router OS - Azriel Christian Nurcahyo; Listra Firgia; Ag. Rudatyo Himamunanto (Informasi Interaktif, 2021)
The use of the internet network since the covid-19 pandemic is increasingly needed as the backbone of the implementation of mobile technology, websites, and desktops where all of them utilize network infrastructure and servers. The use of the right enterprise network combined with adequate server management results in optimal access and stable network conditions. The more complex the network that is built, the more server needs are needed and the more complicated the queuing algorithm that is built to produce the appropriate access speed and optimal storage. Behind these needs, there are several algorithms that can be implemented to optimize the application of enterprise networks.In this study, the implementation of a comparison between the RED, SFQ, and AQM algorithms on RouterOS and VMware ESXi in an enterprise network, in this case a university-scale internet network, is carried out. RouterOS was chosen because most of the networks in the agency, especially using Mikrotik RouterOS for network management and monitoring, while VMware ESXi is used as a virtualization server that can replace many physical servers into one server by implementing virtualization in it to be more practical and efficient. The implementation of the RED, SFQ, and AQM algorithms was tested during March to July and the results showed that the AQM throughput test value was greater than RED and SFQ by 91.4%, the delay and packet loss test values of AQM were better than RED and SFQ by 7% and 8856 ms.Keywords: VMware ESXi, RED, SFQ, AQM,, routerOS.